The Influence of the Problem Based Learning Model Assisted by Learning Video Media on Problem Solving Ability and Mathematical Reasoning of Third Grade Students at SD Negeri 1 Prendengan - Asih Wahyuning; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This research aims to determine: 1) The effect of the Problem Based Learning (PBL) model assisted by learning video media on the mathematical problem-solving abilities of third-grade students at SDN 1 Prendengan; 2) The effect of the Problem Based Learning (PBL) model assisted by learning video media on the mathematical reasoning abilities of third-grade students at SDN 1 Pendengan; 3) The effect of reasoning ability on the mathematical problem-solving abilities of third-grade students at SDN 1 Pendengan.This research was conducted on 47 students. Based on its approach, this research is quantitative.The type of research used in this study is quantitative research with a research design that employs Quasi Experimental Design, specifically the Post-test Only Control Design.In this design, both the experimental group and the control group are compared.The results of the implementation of the experimental class learning, which began with the provision of problems, showed a significance value of 0.000, which means less than 0.05.Thus, Ho is rejected, meaning there is an influence of Problem Based Learning on problem-solving ability.From the table, it can be seen that the R square value is 0.685.This means there is an influence of 68.5% from the use of the Problem-Based Learning model. From these findings, it indicates that the PBL model assisted by learning videos can be an alternative learning model to develop students' problem-solving and mathematical reasoning abilities.